Is the information sufficient?

Geometry Level 4

In the diagram, A C = 1 AC=1 , where C C is the midpoint of side A B AB of triangle A B J ABJ . Square B C D E BCDE is drawn, where D D lies on side A J AJ and E E is in the interior of the triangle. Square F G I H FGIH is drawn, where G G lies on side B J BJ , H H lies on side A J AJ , I I is in the interior of the square, and E E is the midpoint of F G FG .

Find the area of triangle A B J ABJ .


The answer is 3.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

Marta Reece
Mar 6, 2017

C A D = 4 5 \angle CAD=45^\circ , therefore D F = F H DF=FH .
F E = F G 2 = F H 2 = D F 2 FE=\frac{FG}{2}=\frac{FH}{2}= \frac{DF}{2} , so the segment D E DE is divided in thirds with D F = 2 3 DF = \frac{2}{3} and F E = E G = 1 3 FE = EG=\frac{1}{3} .
This will give us ratio of E B E G = 3 \frac{EB}{EG}=3 .
Triangle J B K JBK is similar to triangle B G E BGE so J K B K = 3 \frac{JK}{BK}=3 .
But J K = A K JK=AK because of the 4 5 45^\circ angle, so 3 a = 2 + a 3a=2+a and a = 1 a=1 . The height of triangle A B J = 3 a = 3 ABJ=3a=3 and the area is also 3 3 .


Moderator note:

Great usage of similar triangles to gain more information from the diagram.

Exactly the "nice", non-trigonometrical solution I was looking for!

Dan Ley - 4 years, 3 months ago

Ooohh, filling in that "missing triangle" allows us to work directly with the numerous similar triangles :)

Very nice!

Calvin Lin Staff - 4 years, 3 months ago

Why does fe=df/2?

John Hannah - 4 years, 3 months ago

Log in to reply

If you look at the equation, it says FE = FH / 2 = DF / 2.

The first equation follows because E is the midpoint of the square. (It might be clearer to say FE = FG / 2 = FH / 2 )

The second equation follows from line 1 of DF = FH.

Calvin Lin Staff - 4 years, 3 months ago

Log in to reply

I made the suggested correction.

Marta Reece - 4 years, 3 months ago

Why is BEG similar to BJK?

Ugnė Baronaitė - 4 years, 3 months ago

Log in to reply

They are both made of a vertical side, a horizontal side, and a side at slant. They share the slanted side, BJ shortened to BG, so this side, being the same line, must make the same angles with the horizontal and vertical lines. Specifically EG corresponds to BK, EB to KJ, and BG to JB.

Marta Reece - 4 years, 3 months ago

I love the way you used the similar triangles at the end. I created an infinite series and solved that, then smacked my head against the desk when I saw your solution :)

Nick Maslov - 2 years, 5 months ago
Christian Daang
Feb 24, 2017

Hence, the height of the triangle is given by: 1 + 2 3 + 4 9 + . . . = 3 1 + \cfrac{2}{3} + \cfrac{4}{9} + ... = 3

And therefore, the area of the triangle is: 3 × 2 2 = 3 \cfrac{3 \times 2}{2} = \boxed{3} .


Solution behind the height of the triangle.

Since the triangle ACD is a isosceles right triangle and DF // AC, hence, DAC = HDF = 4 5 \angle \text{DAC} = \angle \text{HDF} = 45 ^ {\circ} .

Let FE = x . F G = F H = F D = 2 x \implies FG = FH = FD = 2x .

By Whole-Part Theorem, FD + FE = BC = 1 x = 1 3 \implies x = \cfrac{1}{3} and hence, the side of square FGIH = 2x = 2 3 \cfrac{2}{3} .

The side of the smaller square ( i.e. 4 9 \cfrac{4}{9} is also obtained by doing these method. )

Now, as you observed, the sides of the square forms a infinite geometric progression, which when you add it all, it is equal to the height of the triangle.

The rest of the solution is given above. 😀😀

Nice setup.

Ideally, the solution should allow those who couldn't solve it to understand what you did. Can you provide a few more details like why D F = 2 3 DF = \frac{2}{3} .

Calvin Lin Staff - 4 years, 3 months ago

Log in to reply

Sir, what do you think of the updated solution? 😄😄.

Christian Daang - 4 years, 3 months ago

Log in to reply

Much better!

Calvin Lin Staff - 4 years, 3 months ago

No need of infinity and beyond. K . I . P . K . I . G K.I.P.K.I.G

Vishwash Kumar ΓΞΩ - 4 years, 3 months ago

I like this problem.

Peter van der Linden - 4 years, 3 months ago

good problem as well as the solution ,i used the same approach .

and make sure you replace the square F G H I FGHI by F G I H FGIH . because F G H I FGHI is an hyperboloid not a square

Syed Hissaan - 4 years, 3 months ago

Did the same way

I Gede Arya Raditya Parameswara - 4 years, 3 months ago

Do you mean point I is in the interior of the triangle, or on the perimeter of the square, because point I certainly isn't inside square HIGF.

Daniel Xian - 2 years, 6 months ago
Aareyan Manzoor
Mar 8, 2017

we can see line F E FE satisfies two eqns: { D F + F E = 1 2 F E = D F \begin{cases} DF+FE=1\\ 2FE=DF\\ \end{cases} the first eqn is true since the two segments are just part of another segment with length 1, the second is true since it is similar to triangle δ A D C \delta ADC , meaning it is isosceles. we can solve to get F E = 1 3 FE=\frac{1}{3} . we consider two similar triangles: A B J , D G J ABJ, DGJ . we can see that [ D G J ] [ A B J ] = ( D G A B ) 2 = ( 1 + 1 3 2 ) 2 = 4 9 \dfrac{[DGJ]}{[ABJ]} = \left(\dfrac{DG}{AB}\right)^2 = \left(\dfrac{1+\frac{1}{3}}{2}\right)^2=\dfrac{4}{9} the area of the trapazoid [ A B G D ] = D C ( D G + A B ) 2 = 5 3 [ABGD] = \dfrac{DC(DG+AB)}{2}=\dfrac{5}{3} we can see [ D G J ] + [ A B G D ] = [ A B J ] [DGJ]+[ABGD]=[ABJ] let v = [ A B J ] v= [ABJ] . then 4 9 v + 5 3 = v v = 3 \dfrac{4}{9} v+\dfrac{5}{3}= v\to v= \boxed{3}

I think there's a typo when comparing the area of two similar triangles, it should be 4 9 \frac{4}{9} instead of 4 3 \frac{4}{3} , but the latter part is written correctly :)

Christopher Boo - 4 years, 3 months ago

Log in to reply

thanks, i have edited the solution.

Aareyan Manzoor - 4 years, 3 months ago

sideways upvote

Dan Ley - 4 years, 3 months ago
Arjen Vreugdenhil
Mar 11, 2017

Similar triangles and squares: A B J D G J ; B C D E G F H I ; A C D D F H . \triangle ABJ \sim \triangle DGJ;\ \ \ \ \square BCDE \sim \square GFHI;\ \ \ \ \triangle ACD \sim \triangle DFH.

From A C = C B AC = CB it follows that D F = F G DF = FG . On the other hand, D F + 1 2 F G = 1 DF + \tfrac12 FG = 1 . From this we conclude D F = 2 3 , DF = \tfrac23, which is also the ratio of similarity, x = 2 3 x = \tfrac23 .

We could continue to build smaller squares on top of the existing square, in the same manner. The top of this infinite tower converges to point J J . Thus the height of J J above base A B AB is y = 1 + x + x 2 + = 1 1 x = 1 1 2 3 = 3. y = 1 + x + x^2 + \cdots = \frac1{1-x} = \frac1{1-\tfrac23} = 3. The area of the triangle is therefore 1 2 A B y = 3 . \tfrac12\cdot AB \cdot y = \boxed{3}.

Nicely presented! It helps that the ratios of similarities of the triangles and the squares is the same.

I liked how you found the height of J J above base A B AB by placing similar squares with sides in a geometric progression. Another way to find the total area of the triangle, but along similar lines, is to find areas of similar trapeziums.

We start with A B G D ABGD , which has area 2 + 4 3 2 × 1 = 5 3 \frac{2 + \frac{4}{3} }{2} \times 1 = \frac{5}{3} . The next trapezium D G I H DGIH would have 4 9 \frac{4}{9} the area of A B G D ABGD . Continuing this, we get total area of 5 3 ( 1 + 4 9 + 4 2 9 2 + ) = 5 3 × 9 5 = 3 \frac{5}{3} (1 + \frac{4}{9} + \frac{4^2}{9^2} + \cdots )= \frac{5}{3} \times \frac{9}{5} = 3 .

Pranshu Gaba - 4 years, 2 months ago
Daniel Liu
Mar 12, 2017

Note that the homothety mapping F G I H FGIH to C B E D CBED has center at the intersection of D H DH and B G BG , which is just J J . Since E E is mapped to the midpoint M M of C B CB with respect to this homothety, then J , E , M J, E, M are collinear. Let h h be the length of the altitude from J J to line D E DE , and let h h' be the length of the altitude from J J to A B AB . Note that h h = B E = 1 h'-h=BE=1 . By similar triangles J D E J A M \triangle JDE \sim\triangle JAM , it follows that h h = D E A M = 1 1 + 1 2 = 2 3 \dfrac{h}{h'} = \dfrac{DE}{AM} = \dfrac{1}{1+\frac{1}{2}} = \dfrac{2}{3} h = 3 2 h = 3 2 ( h 1 ) = 3 2 h 3 2 1 2 h = 3 2 h = 3 \implies h' = \dfrac{3}{2}h = \dfrac{3}{2}(h'-1)=\dfrac{3}{2}h'-\dfrac{3}{2}\implies \dfrac{1}{2}h'=\dfrac{3}{2}\implies h'=3 Thus, the area of A B J \triangle ABJ is 1 2 A B h = 1 2 2 3 = 3 \dfrac{1}{2}\cdot AB\cdot h' = \dfrac{1}{2}\cdot 2\cdot 3=\boxed{3} done.

Note that this solution is particularly nice in that it works with the exact same calculations no matter what length A C AC was; in particular, it does not rely on the fact that C A D = 4 5 \angle CAD=45^{\circ} in any way. \Box

Oh wow! I wasn't expecting a homothety solution to a problem like this. Very unusual yet elegant!

Is homothety your goto move when you see this problem? I would never have thought about this...

Pi Han Goh - 4 years, 3 months ago

Log in to reply

I've been practicing Olympiad Geometry for the past year or two, so I think I have developed an eye for synthetic methods :)

Daniel Liu - 4 years, 2 months ago
Lohith Tummala
Mar 11, 2017

Essentially, the answer is the height of the triangle. If point A is the origin then we can create two lines y=x and y=3x-6. They intersect at a point with a y value of three, so that is the answer

Good use of coordinate geometry. Could you explain how you found the equations of the lines, especially the y = 3 x 6 y = 3x - 6 line? That seems to be the key point of this problem.

Pranshu Gaba - 4 years, 3 months ago
Nazem BouGhannam
Mar 9, 2017

Triangles ACD and BCD are two equal right isosceles then triangle ABD is also right isosceles. Then C A D = 4 5 \angle CAD=45^\circ which means G D H \angle GDH is also 4 5 45^\circ (alternate angles) and H G D = 4 5 \angle HGD = 45^\circ then triangle DGH is right isosceles at H (since it has two 4 5 45^\circ angles) but [HF] is a height of it then it is a median which means D F = F G = 2 F E DF=FG =2FE therefore D F + F E = 1 DF+FE=1 then 3 F E = 1 3FE=1 therefore F E = 1 3 FE = \frac{1}{3} then D G = 4 F E = 4 3 DG=4FE= \frac{4}{3} . Now, ( A B ) ( D G ) (AB) || (DG) then D G A B = 4 3 2 = 2 3 \frac{DG}{AB}=\frac{\frac{4}{3}}{2}=\frac{2}{3} then J D J A = 2 3 \frac{JD}{JA}= \frac{2}{3} then J A = 3 D A JA=3DA , but A D = 2 AD = \sqrt{2} (Pythagorean Th.) then A J = 3 2 AJ=3\sqrt{2} Therefore Area of Triangle A B J = 1 2 B D × A J = 2 × 3 2 2 = 3 ABJ=\frac{1}{2}BD \times AJ = \frac{\sqrt{2} \times 3\sqrt{2} }{ 2} = 3 .

Nice observation that B D BD is perpendicular to A J AJ . It lets us use A J AJ as the base of the triangle for calculating the area.

I didn't understand how you found out H G D = 4 5 \angle HGD =45^\circ before knowing that D F = F G DF = FG . Could you please explain that part?

Pranshu Gaba - 4 years, 3 months ago
Avi Akad
Mar 8, 2017

After we find that EG = 1/3 we know that EB = 1 then we can find the angle <GBE by doing Tan<GBE = 1 / 3 1 \frac{1/3}{1}

<GBE = 18.43

therefore <JBA = 90 + 18.43

<JBA = 108.43

we know that <A = 45

we can find <J which is 180 - 45 - 108.43

<J = 26.56

now we can find the length of AJ by doing

A J s i n 108.43 \frac{AJ}{sin108.43} = 2 s i n 26.56 \frac{2}{sin26.56}

Which gets us to AJ = 4.2435

and so after we find AJ we can calculate the area by the formula ( A J A B s i n < A ) 2 \frac{(AJ * AB * sin <A)}{2} 4.2435 2 s i n 45 2 \frac{4.2435 * 2 * sin45}{2} which gets us to 3.000.

Because this solution is based heavily on numerical approximations. Let me ask you this: You have only ensured that the first three digits after the decimal is 0, how does that tell you that the answer is indeed 3 and not something like 3.0001?

Agnishom Chattopadhyay - 4 years, 3 months ago
Tom Capizzi
Mar 5, 2017

Suppose we construct line segments between D and B and between H and G. Since AC = CD, angle CAD is 45 degrees. So is angle CBD, since segment DB is the diagonal of a square, and bisects a 90 degree angle. Similarly, angles FDH and FGH are also 45 degrees.This means that the square constructed in triangle DGJ is the same proportion to the square inside triangle ABJ as the triangle DGJ is to triangle ABJ. This construction can therefore be continued ad infinitum. As the upper right corner of the square is always interior to the triangle, it asymptotically approaches vertex J. If we now draw a line through all these corners through the baseline, it is clear that it must bisect segment BC at point K, since E bisects FG, and the fact that all the squares are constructed similarly. The tangent of angle IEG is 2, so it must also be the tangent of angle JKB. Finally, we drop a perpendicular to an extension of the baseline, intersecting at point L. Since AL = JL, and KL = 1/2 JL, KL = 1/2 AL. AL = AC + 1/2 BC = 1.5, so AL = JL = 3. The area of triangle ABJ is 2 * 3 / 2 = 3.

Since AC = CD, angle CAD is 45 degrees.

AC = CD is not given. How did you deduce it.

I think you are going at a different approah that others which is really nice. It'd help others to undersand if you put up a diagram.

Agnishom Chattopadhyay - 4 years, 3 months ago

Log in to reply

A C = C D AC=CD because C B E D CBED is a square, and we know A C = C B AC=CB .

Daniel Liu - 4 years, 3 months ago

Very simple:

AB = 2, DG = 4/3, vertical distance between AB and DG = 1. Assume vertical distance between DG and Jamal = x.
DG/AB = x / (x + 1)
x/(x+1) = 4/3/2 = 2/3
3x = 2x + 2
Solving for x, x = 2



height = 3

Area = 1/2 × 2 × 3 = 3

It is not clear to me why is DG equal to 4/3. Could you please explain how you got this result?
Also, do you mean to say J instead of Jamal?

Pranshu Gaba - 4 years, 3 months ago

@Pranshu We can see that DFG maintains the same proportions as ABC. Since B is the midpoint of ABC, F must be the midpoint of DFG.

For easy visualization, we can add a point Q at the midpoint of DF, so that DG is now broken into 4 equal segments, and Since we know DE = 1, and is 3 segments long, each segment = 1/3. Thus, the 4 segments together must be 4/3.

Randy Field - 4 years, 3 months ago

Log in to reply

Oh yes, I get it now. Thanks for explaining :) I didn't realize that the two squares are similar in the same ratio as the triangles JDG and JAB

Pranshu Gaba - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...